Empowering Hospital Infection Control Teams to Optimize Monitoring of Nosocomial Infection Prevention Efforts - Martianawati (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
Nosocomial infections remain a major health problem in hospitals,causing increased patient morbidity and mortality. Effective monitoringand prevention by the Hospital Infection Control Team (PKRS) areessential to reduce these infections. This community service programempowered 15 PKRS members through training, Standard OperatingProcedure (SOP) simulations, and post-training mentoring. Pre- andpost-tests were used to measure knowledge improvement, whilepractical assessments evaluated compliance with infection controlprotocols. Participants demonstrated a 38% average increase inknowledge scores. Observations showed improved adherence torevised SOPs and successful implementation of a new internal audit toolfor infection monitoring. The empowerment approach enhanced boththeoretical understanding and practical skills, fosteringinterdisciplinary collaboration and strengthening the hospital’s infectionprevention system. Continuous mentoring contributed to sustainableimprovements in infection control practices